Kepemimpinan Transformasional dalam Pesantren: Inspire A New Generation - Ikhsan Huzali; Muhammad Sidiq Purnomo (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
This research aims to explore how transformational leadership is implemented in Islamic boarding schools and how it contributes to improving the quality of education. The research results show that Islamic boarding schools implement transformational leadership by inspiring and motivating all members of the Islamic boarding school community to achieve common goals. This is done through various strategies, including the first, namely human resource development: Islamic boarding schools hold regular training for Asatidz administrators and councils to increase their professionalism in managing Islamic boarding schools and educating students. They are also given the opportunity to attend seminars and workshops outside the Islamic boarding school. The second is motivation and inspiration for students: Islamic boarding schools design various programs to inspire students, such as inter-student mentoring programs and activities inviting inspirational figures. They also provide various extracurricular activities to help students discover and develop their interests and talents. The third is increasing participation in the Islamic boarding school community: Islamic boarding schools hold regular discussion forums involving students, Islamic boarding school administrators and parents. This forum is a forum for sharing ideas, input and concerns that affect the Islamic boarding school as a whole.These strategies have proven effective in improving the quality of education in Islamic boarding schools. Santri show increased academic and non-academic achievements, and they are more motivated to achieve their potential. The Islamic boarding school community is also more involved in supporting Islamic boarding school programs. Transformational leadership is an important factor in improving the quality of education in Islamic boarding schools. By implementing the right strategy, Islamic boarding schools can create an inspiring and innovative environment for all components within them, and help students to develop optimally in various aspects of life and education.